The Effect of Gadget Use on Elementary School Students' Social Interaction Abilities - Ayubi, Thariq Al; Desyandri, Desyandri; Irdamurni, Irdamurni (Postgraduate School, Universitas Negeri Padang, 2023)
This research uses a qualitative approach and a literature study. This research aims to analyze the influence of gadget use on elementary school students' social interaction abilities. Researchers collect data from this research by collecting and reviewing consistent data from previous researchers. The results of this research are the influence of gadget use on elementary school students' social interaction abilities. Online learning has an impact on student development starting from enthusiasm for learning, values, and even student personality. Gadgets can also efficiently influence children's social interactions in their immediate area. Not only that, he will also feel unfamiliar with the surrounding area due to the lack of social interaction, not only that, the child will also be less sensitive and even tend not to care about his environment.